Antimicrobial Activity of Vetiveria Zizanioides Mediated Silver Nanoparticles - Rajkumar, Kaushik; Arthanari, Abirami; Rajeshkumar, S (Journal of Neonatal Surgery, 2025)
Introduction: Vetiver roots contain fragrant essential oil, which is a perfume by itself. Aroma chemicals such as vetriverol, vetriverone and vetiveryl acetate are prepared from this volatile oil. In India it is mainly used in perfumes, cosmetics, aromatherapy, food and flavouring industries. Since the plant has extensive finely structured fibrous roots, it is useful in both soil and water conservation and the plant itself is drought tolerant.The aim of this study is to find the antimicrobial activity of vetiveria zizanoides mediated silver nanoparticles. Materials and Method: Vetiveria zizanoides was obtained from the local market and was made to dry in a shady region to finalize the moisture content. After this, they were crushed to fine powder using a grinder. Silver nanoparticles are synthesized and characterized.Antimicrobial activity of the nanoparticles have been analyzed by measuring the zone of inhibition for each microbe based on the concentration of nanoparticles. Results and Discussion: The results obtained in previous study show lesser than the standard values for each bacteria than the antibiotics tested which is similar to the present study.Thus, the compounds with lower antibacterial activity may still have an important role in the development of antibacterial drugs that can be used particularly for children and for the treatment of non-severe infections.For S mutans the zone of inhibition was 13mm for 100µL which is same as the standard antibacterial value. Conclusion: Based on the results,it can be concluded that the silver nanoparticles extracted from vetiveria zizanioides have a moderate level of antibacterial effect.